Effect of coronavirus disease 2019 on recurrences and follow up of head and neck squamous cell carcinoma - Kytö Eero; Haapio Eeva; Kinnunen Ilpo; Irjala Heikki (Cambridge University Press, 2022)
Objective. This prospective study aimed to evaluate possible diagnostic delays in head and neck squamous cell carcinoma recurrences due to the changed follow-up protocol during the coronavirus disease 2019 pandemic.
Methods. The follow-up appointments of head and neck squamous cell carcinoma patients treated more than one year prior to the pandemic were changed to telephone appointments in order to reduce physical visits to the hospital. All contacts, reasons for contact and recurrent cancers were recorded.
Results. There were 17 recurrences during a seven-month study period among 178 patients treated in the previous year (10 per cent); 14 of these recurrences occurred in patients whose treatment had ended less than one year previously and 3 occurred more than one year after treatment had ended. There was no delay in diagnoses of recurrent tumours or treatment despite reduced visits because of the coronavirus disease 2019 pandemic.
Conclusion. According to our analyses, no delay was caused in the diagnoses of recurrent diseases. Follow up by telephone or telemedicine can be considered as part of the follow-up protocol one year after the treatment of head and neck squamous cell carcinoma when necessary.